Tvetenia vitracies (Sæther, 1969), a synonym of Tvetenia tshernovskii (Pankratova, 1968), comb. n. (Diptera: Chironomidae) - Przhiboro, Andrey A.; Sæther, Ole A. (Zootaxa, 2010)
Type material of Eukiefferiella tshernovskii Pankratova, 1968 is re-examined, and the lectotype is designated. The characters of E. tshernovskii fit the diagnosis of the genus Tvetenia Kieffer, 1922. Consequently, a new combination and synonymy are established, Tvetenia tshernovskii (Pankratova, 1968), comb. n. = T. vitracies (Sæther, 1969), syn. n. Diagnostic characters of the larva of T. tshernovskii are emended. Nomenclatural notes on the species are given, and its distribution and bionomics are briefly reviewed.